Flowing Stream Strategy Leveraging Strategic Change with Continuity. - Sushil; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2013)
Though the concern regarding the confluence of continuity and change is well accepted, there is hardly any well known framework in the literature that can be used as a benchmark to deal with this paradoxical issue. Keeping in view the significance of the topic and the lack of practical frameworks in managing continuity and change this book is an endeavor to fill the gap. The main proposition of the book is that the strategic management of change could be better leveraged with clear understanding of continuity of the organization and consciously managing the vital and desirable areas of continuity along with change, rather than leaving the continuity to be managed by default. The continuity of any company provides the bedrock along which the flow of change could be channelized. It adopts flowing stream as the principal metaphor for continuity and change to be taken side by side. It can be treated as a stepping stone to inspire a lot of research in this area.
Part I Opening the Door -- Part II Continuity and Change: Laying the Foundation -- Part III Fundamentals of Flowing Stream Strategy (Principles, Frameworks, and Strategies) -- Part IV Making Flowing Stream Strategy Work (Methodology, and Tools) -- Part V The Practice of Flowing Stream Strategy -- Part VI Looking Beyond -- References -- Appendices -- Index.
Keywords: Economics; Industrial management; Business planning; Economics/Management Science; Management/Business for Professionals; Administration, Organization and Leadership; Organization/Planning.